Technological innovation for resilient systems : 9th IFIP WG 5.5/SOCOLNET Advanced Doctoral Conference on Computing, Electrical and Industrial Systems, DoCEIS 2018, Costa de Caparica, Portugal, May 2-4, 2018, Proceedings /: 9th IFIP WG 5.5/SOCOLNET Advanced Doctoral Conference on Computing, Electrical and Industrial Systems, DoCEIS 2018, Costa de Caparica, Portugal, May 2-4, 2018, Proceedings. (2018) - Unknown
No abstract available